Upgrading Iron and Removing Phosphorus of High Phosphorus Oolitic Iron Ore by Segregation Roasting with CaCl2+Ca(ClO)2 - Tiefeng, Peng (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The iron-bearing ore, existing in the form of oolite, was mainly composed of hematite, limonite, daphnite and collophane. Harmful element phosphorus content was 1.56%, belonging to high phosphorus oolitic iron ore in western Hubei. In this study, segregation roasting and low intensity magnetic separation techniques were applied to upgrading iron and removing phosphorus. The ores, chlorinating agent and reducing agent were mixed into the roasting furnace for segregation roasting. After being transferred from weak magnetic minerals to the strong ones, the iron was recovered by low intensity magnetic separation. During segregation roasting, new ore phases, metallic iron (Fe), small amount of ferroferric oxide (Fe3O4) and ferrous oxide (FeO) can be observed. Results showed that iron concentrate with Fe content of 90.3%, phosphorus content of 0.15%, iron recovery of 92.9% were obtained under segregation roasting temperature 1273 K, roasting time 90 min, CaCl2 (calcium chloride) 20%, Ca(ClO)2 (calcium hypochlorite) 3%, dosage of coke 20%, low intensity magnetic separation field intensity 0.12 T.